Size-Mediated Interaction between a Cushion Species and Other Non-cushion Species at High Elevations of the Hengduan Mountains, SW China - Yang, Yang; Chen, Jian-Guo; Schöb, Christian; Sun, Hang (Frontiers in Plant Science, 2017)
Arenaria polytrichoides (Caryophyllaceae) is a common cushion plant occurring at high elevations in the Himalaya-Hengduan Mountains, SW China. It frequently has other non-cushion species growing within its canopy, forming a contrast with the surrounding areas because it creates patches of higher diversity and greater biomass. In this study, we examined the relationship between the cushions and associated non-cushion species along a gradient of cushion size. A total of 200 A. polytrichoides individuals were selected to fit four size classes. Field measurements were carried out to assess canopy structure, functional traits relevant to growth and reproduction, and soil quality below cushions along the size gradient. Furthermore, the size effect of cushions on the richness and abundance of species and biomass production was also examined. All the morphological variables examined exhibited a positive correlation with cushion size, as did the nutrients under cushions. Large and compact cushions were associated with higher soil nutrient contents compared with small and loose cushions. As a result of these biogenic environmental changes, there was a stronger facilitation effect performed by large cushions. Data pertaining to functional traits revealed that large cushions benefit from the enhanced resources within their compact structure and exhibit greater fitness and a higher reproductive output than small cushions. Our data indicated that interactions occur between cushion species and other plants depending on the size of the cushions, probably because of the greater heterogeneity of conditions beneath larger cushions. These findings provide a clear demonstration of the generally overlooked importance of the traits of nurse plants, such as size and age, in terms of their facilitative effects.